65.4k views
5 votes
Solve 3^(x+1) = 15 for x using the change of base formula

2 Answers

3 votes


\bf \textit{Logarithm of exponentials} \\\\ \log_a\left( x^b \right)\implies b\cdot \log_a(x) \\\\\\ \textit{Logarithm Change of Base Rule} \\\\ \log_a b\implies \cfrac{\log_c b}{\log_c a}\qquad \qquad c= \begin{array}{llll} \textit{common base for }\\ \textit{numerator and}\\ denominator \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}


\bf 3^(x+1)=15\implies \log_(10)(3^(x+1))=\log_(10)(15)\implies (x+1)\log_(10)(3)=\log_(10)(15) \\\\\\ x+1=\cfrac{\log_(10)(15)}{\log_(10)(3)}\implies \stackrel{\textit{change of base rule}}{x=\cfrac{\log_(e)(15)}{\log_(e)(3)}-1}\implies x\approx 1.47

User Jgoeders
by
6.3k points
5 votes

Answer:


x=(log(15))/(log(3))-1

Explanation:


3^(x+1) = 15

LEts convert exponential form to log form


b^x=a can be written as
log_b(a)=x

WE apply the same rule to convert the given exponential form to log form


3^(x+1) = 15


log_3{15} = x+1

HEre the base of log is 3. Lets apply change of base formula


log_b(a)=(log(a))/(log(b))


log_3{15} = x+1


(log(15))/(log(3)) = x+1

Now subtract 1 from both sides


x=(log(15))/(log(3))-1

User Danvitoriano
by
6.0k points